Chilling to the bone: Lower temperatures increase vertebrate predation by tonatia bidens (chiroptera: Phyllostomidae) - Carvalho, Fernando (2020)
The greater round-eared bat, Tonatia bidens (Spix, 1823), is a medium-sized phyllostomid bat distributed in the north of Argentina, Paraguay and Brazil. The diet and foraging patterns of this species are poorly known. We analyzed the composition of the diet of a population of T. bidens and how the temperature influences the consumption of vertebrates and invertebrates. To describe diet composition, we conducted weekly collections of food scrap from two monospecific night-perches. Data of temperature for the study period were taken from the meteorological station installed 300 m from the collection perches. The influence of temperature was evaluated using generalized linear models (GLMs) with negative binomial distribution. Tonatia bidens consumed 28 taxons (204 records), being at least 17 Artropods and 11 Passeriformes birds. Temperature explained a greater proportion of vertebrate abundance (R2 = 0.23) than invertebrate (R2 = 0.16) or to both pooled (R2 = 0.11). The relation with temperature was positive with invertebrates and negative with the vertebrates. The diet of the population of T. bidens comprised mainly invertebrates, which were the most frequent and diverse taxa. Data suggests that T. bidens has a diverse diet, with proportion of the item’s consumption varying temporally. Environmental factors, such as the temperature presented on this work, seems to be good proxies for the dietary traits of this species. © 2020 Sociedade Brasileira de Zoologia.